Minimum inhibitory concentration of the plant extracts' combinations against dental caries and plaque microorganisms: An in vitro study - B R Chandra Shekar; Ramesh Nagarajappa; Richa Jain; S Suma; Rupal Singh; Rupesh Thakur (Wolters Kluwer Medknow Publications, 2016)
Introduction: Oral health status has witnessed marked advances in many industrialized countries. However, dental caries is consistently increasing in developing countries, and periodontal diseases are among most common afflictions to humankind. Approach best suited for developing countries is to focus on the prevention with innovative strategies. Hence, evolution of novel, innovative strategies to prevent dental caries and periodontal diseases is need of hour. Objective: To determine minimum inhibitory concentration (MIC) of combinations of Acacia nilotica, Murraya koenigii L. Sprengel, Eucalyptus hybrid, and Psidium guajava against dental caries and plaque microorganisms and to qualitatively identify various phytochemical constituents in individual plant extracts and their quadruple combinations. Materials and Methods: MIC of the combinations of A. nilotica, M. koenigii L. Sprengel, Eucalyptus hybrid, and P. guajava on Streptococcus mutans, Lactobacillus acidophilus (dental caries bacteria), Streptococcus sanguis, Streptococcus salivarius (primary plaque colonizers), Fusobacterium nucleatum (secondary plaque colonizer), and Porphyromonas gingivalis (tertiary plaque colonizer) was determined using broth dilution method. Series of dilutions of quadruple combinations ranging from 0.05% to 1.5% were prepared. 100 μL of each serial dilution of quadruple combinations was added to each tube containing bacterial culture. The optical density was noted after incubation in each tube to estimate the MIC for each bacterium. Results: MIC of the polyherbal combinations on S. mutans, S. sanguis, S. salivarius, L. acidophilus, F. nucleatum, and P. gingivalis was found to be 0.25%, 0.05%, 0.05%, 0.1%, 0.25%, and 0.25%, respectively. Conclusion: The quadruple combinations of these four plant extracts could be considered in the evolution of an indigenous polyherbal mouth rinse as the formulation inhibited all the bacteria tested in the present study at low concentrations.